Histopathologic Aspects of Malignancy-Associated Granuloma Annulare: A Single Institution Experience - Buket Bagci; Cansu Karakas; Harsimran Kaur; Bruce R. Smoller (MDPI AG, 2023)
Granuloma annulare (GA) is a benign, self-limiting granulomatous inflammatory disease that exhibits different histologic patterns. Infrequently, granuloma annulare can be associated with malignancy, the so-called malignancy-associated granuloma annulare (MGA). In this study, we aimed to compare the clinical and histopathological differences between GA and MGA. We retrospectively reviewed patient charts and identified 35 patients diagnosed with GA and concurrent hematological or solid organ malignancies as a case group. Additionally, we identified 33 patients without any known solid organ or hematological malignancy as a control group. MGA is commonly seen in the seventh decade of life, while GA affects the younger population. MGA is most commonly presented in the extremities of the body. The most common malignancy associated with MGA was chronic lymphocytic leukemia. Prostate cancer was the most common type of solid organ malignancy that was associated with MGA. The most common histopathological pattern seen in MGA was interstitial, comprising half of the cases. Multinucleated giant cells were present in half of the MGA cases and in most of the control group. In the literature, there are no established features that distinguish MGA from GA. Although MGA and GA have overlapping features, in our series, we found that the interstitial pattern was more common in MGA, while the necrobiotic pattern was more common in GA.